Comparative study in extracorporeal shock wave lithotripsy with and without the use of local anaesthetic (Lidocaine 1%) infiltration at the shock wave site - Nagendra, BKC; Sharma, U (Kathmandu University Medical Journal, 2010)
Background: Extracorporeal Shock Wave Lithotripsy (ESWL) is a simple and non-invasive technique in which renal and ureteric calculi are pulverised into small fragments by shockwaves and then allowed to pass spontaneously in small fragments along with urine. Effective ESWL requires a co-operative patient who will remain immobilize on the lithotripsy table comfortably for which different anaesthetic techniques are used. Occasionally discharge of patient is delayed due to persistent sedation, nausea and vomiting. Objective: The aim is to assess the use of local anaesthetic agent (20 ml Lidocaine 1%) infiltration in 60 patients (Experiment Group) and no infiltration in 60 patients (Control Group) on patients undergoing Extracorporeal shock wave lithotripsy (ESWL) procedure. Materials and methods: is a study done in 120 patients of ASA I and ASA II patients undergoing ESWL procedure. The infiltration technique is standardized so that the local anesthetic agent was infiltrated five minutes before the procedure along the line of shockwave site in Experiment Group. Result: In this study, the age, sex, weight, time of shockwave treatment was almost similar in both groups. The mean need of Ketamine and duration of stay after procedure was significantly more in control group than experiment group. Conclusion: In this study, it is concluded that the need of Ketamine and duration of stay after procedure is significantly more in control group. Key words: ESWL; infiltration; Ketamine; Lidocaine 1% DOI: 10.3126/kumj.v7i2.2697 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 92-96